Copulation with immature females increases male fitness in cannibalistic widow spiders - Biaggio, M. Daniela (Biol Lett, 2016)
Copulatory cannibalism of male ‘widow’ spiders (genus Latrodectus) is a model example of the extreme effects of sexual selection, particularly in L. hasselti and L. geometricus where males typically facilitate cannibalism by females and mate only once. We show that these males can increase their reproductive success by copulating with final-instar, immature females after piercing the female's exoskeleton to access her newly developed sperm storage organs. Females retain sperm through their final moult and have similar fecundity to adult-mated females. This is an adaptive male tactic because immature mating increases insemination success relative to adult mating (which predicts higher paternity) and moreover, rarely ends in cannibalism, so males can mate again. Although successful only during a brief period before the female's final moult, males may employ this tactic when they associate with final-instar females in nature. Consistent with this, one-third of L. hasselti females collected as immatures in nature were already mated. Immature mating alters sexual selection on these otherwise monogynous males, and may explain male traits allowing facultative polygyny in Latrodectus. Since male cohabitation with immature females is common among invertebrates, immature mating may be a widespread, previously unrecognized mating tactic, particularly when unmated females are of high reproductive value.